2021
DOI: 10.1002/jsfa.11244
|View full text |Cite
|
Sign up to set email alerts
|

Suitability and benefits from intercropped sorghum–amaranth under partial root‐zone irrigation

Abstract: BACKGROUND: The production of sufficient animal feed in arid and semi-arid regions plays a significant role in food security in these areas. The present study was conducted based on the hypothesis that intercropping of sorghum and amaranth, comprising relatively drought tolerant forages, will enhance the yield and quality of the feed under limited irrigation water availability. RESULTS: Implementation of fixed alternate furrow irrigation (FFI) and alternate furrow irrigation (AFI) resulted in a saving of 22.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…In the current study, intercropped forage sorghum and amaranth improved dry matter yield and the quality of the forage mix, as long as sorghum constituted 50% of the intercropped system. The results are in agreement with the earlier report indicated that 50:50 intercropping ratio of sorghum and amaranth performed best compared with other ratios 9 . The 50:50 ratio of sorghum and amaranth boosted the forage yield by over 25% compared with high‐yielding monoculture forage sorghum.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, intercropped forage sorghum and amaranth improved dry matter yield and the quality of the forage mix, as long as sorghum constituted 50% of the intercropped system. The results are in agreement with the earlier report indicated that 50:50 intercropping ratio of sorghum and amaranth performed best compared with other ratios 9 . The 50:50 ratio of sorghum and amaranth boosted the forage yield by over 25% compared with high‐yielding monoculture forage sorghum.…”
Section: Discussionsupporting
confidence: 92%
“…33,5 This inefficient irrigation method is well-known for having the lowest application efficiency due to its deep percolation from irrigated fields. 9 Seeking alternative irrigation strategies, identifying lower water demand crops, and adopting more sustainable cropping systems are among the strategies to enhance IWUE. In the case of forage crops, in addition to total biomass yield, the quality of forage which is commonly expressed as energy content or milk value seems more appropriate than just dry matter yield.…”
Section: Effects Of Irrigation Methods On Forage Production and Iwuementioning
confidence: 99%
See 1 more Smart Citation
“…Due to climate change in recent years and the significant yield reduction due to drought stress, it is necessary to identify drought-resistant genotypes (Baghdadi et al, 2021). A comparison between drought tolerance indices and physiological characteristics showed that genotype G8 had the highest Ys, WP, MP, GMP, HM, STI, and YI, and low CT, so it was identified as the most drought-tolerant genotype (Table 6).…”
Section: Figmentioning
confidence: 99%
“…In recent years, climate change and the subsequent increase in the incidents and duration of drought have threatened crop production and food security (Balazadeh et al, 2021;Farhadi et al, 2022). Drought stress is one of the most significant factors limiting crop yield, it has different effects at different stages of plant development and profoundly affects agricultural systems and food production (Golzardi et al, 2017;Ashoori et al, 2021;Baghdadi et al, 2021). However, rice requires a large amount of water for its growth and development (Sabouri et al, 2022), and drought is the most critical limiting factor for rice growth and production (Pandey and Shukla, 2015).…”
Section: Introductionmentioning
confidence: 99%